He’s a Real Man - Grace Shih MD, MAS (American Journal of Men's Health, 2013)
Vasectomy has advantages with respect to safety and cost when compared with female sterilization. The reasons underlying the overall low use of vasectomy, particularly among Black and Latinos, have not been adequately explored. The goals of this study were to (a) explore the social context of vasectomy decisions and (b) generate hypotheses about the social factors contributing to differences in vasectomy use by race/ethnicity. Fourteen group and nine couples interviews were conducted. Participants were 37 heterosexual couples aged 25 to 55 years who had reached their desired family size and self-identified as Black, Latino, or White. Participants discussed reasons that men and women would or would not select male sterilization. Reasons to select vasectomy included a desire to care for their current family, sharing contraceptive responsibility, and infidelity. Reasons not to select vasectomy included negative associations with the term sterilization , loss of manhood, and permanence. Misconceptions about vasectomy included misunderstandings about the vasectomy procedure and adverse postvasectomy sexual function. In addition, Black and Latino participants cited perceived ease of reversibility of female sterilization and lack of support around vasectomy as reasons not to choose it. Improving communication and social support for vasectomy, particularly among Black and Latino communities, may improve vasectomy utilization. Misconceptions regarding female and male sterilization should be targeted in counseling sessions to ensure men, women, and couples are making informed contraceptive decisions.